Antioxidant and/or antimicrobial composition based on palm oil - Lai, Oi Ming; Tan, Chin Ping; Lai, Wee Ting; Khong, Nicholas Mun Hoe; Voon, Phooi Tee (2014)
The present invention discloses an antimicrobial, antioxidant and natural preservative comprising of palm-derived carotenoid rich oil, including but not limited to, red palm oil and it’s fractions that could be in the form of whole and/or neat oil (non-processed oil), fractionated fractions and/or extracts as well as mixtures and/or formulations with other oils such as virgin coconut oil. The invention also discloses the uses of the carotenoid rich oil/ fraction and/ or therapeutically effective amount of carotenoid rich oil/ fraction which has high antioxidant and antimicrobial activity as an antioxidant, antimicrobial and/or immune enhancer in food, feed, cosmetics, toiletries, pharmaceuticals and medicines.